Advances in Exploring Cyclopentadienyl (Cp) Rhodium Catalysts Featuring Diastereotopic or Enantiotopic Cp Faces for Asymmetric C–H Activation - Yan, Xiaoqiang; Wang, Jun (Synthesis, 2023)
Chiral cyclopentadienyl rhodium (CpRh) complexes have emerged as a class of powerful catalysts for enantioselective C–H activation reactions. In terms of Cp ligand development, the mainstream is to design chiral ligands with C2 symmetry in order to avoid the problem of Cp face selectivity during their metalation with rhodium. In recent years, CpRh catalysts with diastereotopic or enantiotopic Cp faces were also revealed and successfully applied in asymmetric C–H activation. These advances are summarized in this short review together with perspectives for their future development.1 Introduction2 Cp Ligands with Diastereotopic Cp Faces3 Cp Ligands with Enantiotopic Cp Faces4 Conclusion and Outlook
Keywords: cyclopentadienyl; rhodium; asymmetric C–H activation; planar chiral; diastereotopic Cp face; enantiotopic Cp face; prochiral Cp